Adipose tissue loss during neoadjuvant chemotherapy: a key prognostic factor in advanced epithelial ovarian cancer - Benouali, Wassim; Dolly, Adeline; Bleuzen, Aurore; Servais, Stéphane; Dumas, Jean-François; Vandier, Christophe; Goupille, Caroline; Ouldamer, Lobna (Frontiers in Physiology, 2025)
BackgroundAdvanced epithelial ovarian cancer (EOC) patients often receive neoadjuvant platinum-based chemotherapy (NAC), with interval surgery (after three cycles of chemotherapy) considered as a major prognostic factors. We examined how changes in body composition (muscle and adipose tissue) during NAC influence prognosis.ObjectiveUsing CT images acquired before and during NAC in a cohort of women with advanced EOC, the aim of this study was to analyze body composition (muscle and fat mass) and see whether these parameters, at diagnosis or as they evolve during chemotherapy, can be linked to recurrence-free survival and overall survival (RFS and OS).Material and methodsThe study included 53 patients with FIGO stage III-IV epithelial ovarian cancer. CT images were analyzed to calculate skeletal muscle index (SMI), subcutaneous adipose tissue index visceral adipose tissue index estimated lean body mass (LBM) and estimated whole-body fat mass (WFM). Changes in tissue composition were normalized for 100 days and expressed as % change to account for intervals between scans at baseline and after three cycles of chemotherapy. The impact on survival was assessed by Log-rank test.ResultsAt diagnosis, clinical criteria such as age or BMI did not correlate with RFS or OS. 60% of patients were considered sarcopenic (low SMI), including mainly underweight and normal-weight patients. Low SMI was not associated with RFS or OS. Twenty-six patients who underwent interval surgery demonstrated longer relapse-free intervals (p = 0.01). Notably, while muscle parameters showed minimal changes (−2%), parameters assessing adipose tissue showed significant decreases of 10, 12% and 7.6% per 100 days (VATI, SATI and estimated WFM, respectively). Obese patients were particularly affected by this loss of muscle and fat, compared with patients in other BMI categories. Rapid and severe loss of VATI (−28% per 100 days) and estimated WFM (−18% per 100 days) were significantly associated with shorter OS (p = 0.031 and p = 0.046 respectively).ConclusionOur findings suggests that early and substantial loss of visceral adipose tissue during NAC is a significant predictor of poor survival in advanced EOC. This highlights an urgent need for targeted nutritional or pharmaceutical strategies to mitigate fat loss and improve patients outcomes.